A Comparative Study on the Two Translations of Confucian Analects - Bai, Chun (Journal of Sinology (วารสารจีนวิทยา), 2008)
The aim of this article is to study the translator’s strategy, comprehension in the two translations of Confucian Analects, the most important record of Confucius’s philosophy, and try to seek out the relation between translation strategy, translator’s decision and the outcome.